2023
DOI: 10.3389/fcell.2023.1221890
|View full text |Cite
|
Sign up to set email alerts
|

Neuronal activity and remyelination: new insights into the molecular mechanisms and therapeutic advancements

Abstract: This article reviews the role of neuronal activity in myelin regeneration and the related neural signaling pathways. The article points out that neuronal activity can stimulate the formation and regeneration of myelin, significantly improve its conduction speed and neural signal processing ability, maintain axonal integrity, and support axonal nutrition. However, myelin damage is common in various clinical diseases such as multiple sclerosis, stroke, dementia, and schizophrenia. Although myelin regeneration ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 152 publications
0
15
0
Order By: Relevance
“…These cells represent 75% of all glial cells in the adult CNS. In addition to axonal myelination, OLs control extracellular potassium concentration and, as mentioned above, provide metabolic and trophic supply to myelin, secrete glial and brain-derived neurotrophic factors (GDNF and BDNF), and modulate the axonal growth [ 117 , 122 , 123 ], all of which highlight their importance in the functioning of CNS. Like microglia and astrocytes, OLs also express TLRs, which are considered of significant importance in myelin formation [ 58 , 124 , 125 ].…”
Section: Oligodendrocytesmentioning
confidence: 99%
See 4 more Smart Citations
“…These cells represent 75% of all glial cells in the adult CNS. In addition to axonal myelination, OLs control extracellular potassium concentration and, as mentioned above, provide metabolic and trophic supply to myelin, secrete glial and brain-derived neurotrophic factors (GDNF and BDNF), and modulate the axonal growth [ 117 , 122 , 123 ], all of which highlight their importance in the functioning of CNS. Like microglia and astrocytes, OLs also express TLRs, which are considered of significant importance in myelin formation [ 58 , 124 , 125 ].…”
Section: Oligodendrocytesmentioning
confidence: 99%
“…More recently, it was suggested that NG2 cells play a critical role in the modulation of neuroinflammation [ 131 ] and neurovascular unit formation during development [ 123 ] ( Figure 1 ). Although no TLRs have yet been identified in these cells, their importance in angiogenesis and oligodendrogenesis following acute ischemic stroke was reported [ 132 ].…”
Section: Synantocytes (Ng2 Cells)mentioning
confidence: 99%
See 3 more Smart Citations